Cloud Computing CPU Allocation and Scheduling Algorithms using CloudSim Simulator - Hicham GIBET TANI; Chaker EL AMRANI (International Journal of Electrical and Computer Engineering (IJECE), 2016)
In this paper, we describe the Cloud Computing basic compute resources scheduling and allocation algorithms, in addition to the working mechanism. This paper also presents a number of experiments conducted based on CloudSim simulation toolkit in order to assess and evaluate the performance of these scheduling algorithms on Cloud Computing like infrastructure. Furthermore, we introduced and explained the CloudSim simulator design, architecture and proposed two new scheduling algorithms to enhance the existent ones and highlight the weaknesses and/or effectiveness of these algorithms.